2008
DOI: 10.1016/j.fsigen.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutations in father–son pairs with 17 Y-STR loci

Abstract: We have examined 389 father/son sample pairs from U.S. Caucasians, African Americans, Hispanics and Asians using the 17 Y-STR loci in the Yfiler TM kit and observed a total of 24 differences between father and son. Thirteen mutations resulted in the gain of a repeat in the son and 11 resulted in a loss of a repeat. All samples resulted in single repeat mutations except one sample which contained a two repeat loss at Y-GATA-H4. Furthermore, two different sample pairs were found to have two mutations. An African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 18 publications
3
25
1
Order By: Relevance
“…Two mutations were observed at loci DYS456, DYS393, DYS391 and DYS385. The average mutation rate was 3.66 Â 10 À3 similar to results of other working groups obtained for Y-STRs [9][10][11][12]. All mutations were characterized by sequencing.…”
Section: à3supporting
confidence: 81%
“…Two mutations were observed at loci DYS456, DYS393, DYS391 and DYS385. The average mutation rate was 3.66 Â 10 À3 similar to results of other working groups obtained for Y-STRs [9][10][11][12]. All mutations were characterized by sequencing.…”
Section: à3supporting
confidence: 81%
“…With this aim, we present here the first study of 17 Y-STR loci in autochthonous European Basques and the Basque diaspora in the Western USA. [15]; CA-US Caucasian Americans [13]; HI-US Hispanic Americans [13]; AS-US Asian Americans [13]; AF-US African Americans [13]; POR Portugal [16]; ITA Italy [17]; AUS Austria [18]; GER Germany [19]; POL Poland [19]; ROM Romania [20]; GRE Greece [21]; SER Serbia [22]; CRO Croatia [23] Our results demonstrate a very high-level of conservation of the Y chromosome haplotypes characteristic of the European autochthonous Basque population among individuals of the Basque diaspora in the Western USA. No signs of founder haplotypes have been found, probably because the number of European Basque male individuals who have settled in the Western USA has been large enough for a similar Y-haplotype frequency distribution to be reached between the source and the emigrant populations.…”
Section: Discussionmentioning
confidence: 99%
“…We determined the frequency of Basque surnames in the Western USA Basque diaspora population sample and found that 86% had a paternal Basque surname, while 14% had a non-Basque paternal ancestry. To check for the origin of haplotypes incorporated into the gene pool of the Basque diaspora in the Western USA, we compared the Y-STR haplotypes of the Basque diaspora with those in the Basque source population and with subpopulations from the USA (Caucasians, Hispanics, Africans and Asians) [13].…”
Section: Y-str Haplotypes In the Population Of The Basque Country Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Slight deviations from independence will occasionally be (Decker et al 2008;Goedbloed et al 2009). For human identity testing, Ballantyne and co-authors (2012) purposefully selected rapidly mutating Y STRs to increase the differentiation for male relatives.…”
Section: Autosomal Markersmentioning
confidence: 99%